Debye Screening Effect on Scaling Behavior of Longest Relaxation Time of Biological Polyelectrolyte Chain - Lee, Jeong Yong; Sung, Jung Mun; Yoon, Kyu; Chun, Myung-Suk; Jung, Hyun Wook (KOREAN CHEMICAL SOC, 2013)
The scaling relationship of the longest relaxation time of a single chain of semiflexible biological polyelectrolyte has been investigated by performing well-established coarse-grained Brownian dynamics simulations. Two kinds of longest relaxation times were estimated from time-sequences of chain trajectories, and their behaviors were interpreted by applying the scaling law for different molecular weights of polyelectrolyte and Debye lengths. The scaling exponents for longest stress relaxation and rotational relaxation are found in the ranges of 1.67-1.79 and 1.65-1.81, respectively, depending on the physicochemical interaction of electrostatic Debye screening. The scaling exponent increases with decreasing screening effect, which is a special feature of polyelectrolytes differing from neutral polymers. It revealed that the weak screening allows a polyelectrolyte chain to follow the behavior in good solvent due to the strong electrostatic repulsion between beads.
Keywords: BROWNIAN DYNAMICS SIMULATIONS; SEMIDILUTE POLYMER-SOLUTIONS; SINGLE DNA-MOLECULES; SHEAR-FLOW; CONFORMATIONAL TRANSITION; HYDRODYNAMIC INTERACTIONS; SLITLIKE NANOCHANNELS; MACROMOLECULES; TRANSPORT; DILUTE